2012
DOI: 10.1016/j.ejmech.2012.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and antibacterial activity of minor groove binders: The role of non-cationic tail groups

Abstract: The design and synthesis of a new class of minor groove binder (MGBs) in which, the cationic tail group has been replaced by a neutral, polar variant including cyanoguanidine, nitroalkene, and trifluoroacetamide groups. Antibacterial activity (against Gram positive bacteria) was found for both the nitroalkene and trifluoroacetamide groups. For the case of the nitroalkene tail group, strong binding of a minor groove binder containing this tail group was demonstrated by both DNA footprinting and melting temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The results of antibacterial screening revealed that, in general, the bis-phenyl derivatives (21)(22)(23)(24)(25)(26)(27) Replacement of one amidino-benzimidazole group in symmetrical compounds 18-20…”
Section: Thermal Denaturation Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of antibacterial screening revealed that, in general, the bis-phenyl derivatives (21)(22)(23)(24)(25)(26)(27) Replacement of one amidino-benzimidazole group in symmetrical compounds 18-20…”
Section: Thermal Denaturation Experimentsmentioning
confidence: 99%
“…These antibacterial activity. MICs against sensitive S. aureus are ≤ 0.5 µg/mL for compounds I and II and 6.25 and 50 µg/mL for compound III and distamycin, respectively [12,21,23,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the minor groove is a relevant hydrogen acceptor group that could interact with enzymes, proteins or other active molecules and/or metal complexes. Thus, several promising minor groove binders have showed different biological activities such as antitumoral, antiprotozoal or antibacterial properties [44][45][46][47] and even other approaches regarding gene expression [48]. Therefore the interaction between different organic compounds and/or metal complexes with the N3(purine-like) donor is a topic of increasing interest and encourage further researches regarding the rational design of new biomimetic systems with biological and/or pharmaceutical applications.…”
Section: Metal Binding Of N 6 -Substituted Adenines and Future Develomentioning
confidence: 98%
“…This is in spite of significant efforts in chemical biology for over a decade to find methods to systematically modulate cellular transcription factor activity. Complementing the successful polyamides with compounds that have different recognition modules with enhanced cellular uptake and improved solution properties would be an important major advance in the effort to target specific protein binding to nuclear DNA (1, 7, 2124). …”
Section: Introductionmentioning
confidence: 99%